POLITIK PEMBENTUKAN RANPERDA YANG BERASAL DARI DPRD PROVINSI RIAU ( STUDI KASUS PEMBENTUKAN KEBIJAKAN SISTEM PEMERINTAHAN BERBASIS TEKNOLOGI INFORMASI DAN KETERBUKAAN TAHUN 2015 ) - Hendra Setiawan; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The background of this research is related to the political process of policy formulation based on government systems, telecommunications and openness. The political process in question is the integration of interests between the Regional House of Representatives (DPRD) with the executive in this case the Governor of Riau. Although the process of establishing the local regulation into a Regional Information System based on Information Technology and Openness is relatively fast. There are two formulations of the problem in this study, namely "What is the political process of establishing an information technology regional regulation draft based on openness and transparency by the Riau Provincial DPRD in 2015 and What are the factors that influence the political process of establishing an information technology based regional regulation draft regulation and transparency by the Riau Provincial DPRD 2015 ".This research approach used is a qualitative approach. While the type of research used is descriptive. Data were collected by the authors using interview and documentation techniques. The data used are primary data obtained from research informants and subsequently secondary data obtained from various government agencies related to this study. The results showed that the political process for the drafting of the regional regulation draft based on IT and openness had been carried out in accordance with the rules of the Riau Province Regional House of Representatives. The Drafting of Local Government Regulation on IT-based and Openness Government Systems also neglected aspects of regional government readiness. Even so, the political process of drafting this Regional Regulation into a Regional Regulation is relatively fast and has the support of the Governor and Members of the Riau DPRD. The constraints faced by the DPRD in carrying out its duties and functions in the formation of regional regulations on the initiative of the DPRD on IT-Based Government Systems and Openness are internal and external constraints. Internal obstacles encountered were human resource constraints and political will. Whereas external obstacles encountered were executive dominance (executive heavy) and other assignments.